Комплекс знахідок черняхівської культури з поселення біля с. Лук’янівка - Романюк, В.В. (Археологія, 2003)
У публікації подано матеріали з нової пам’ятки черняхівської культури — поселення біля с. Лук'янівка. Таращанским археологическим клубом «Неврида» при районном ЦТДЮ на протяжении последних лет проводятся археологические разведки у с. Лукьяновка Таращанского р-на Киевской обл. На западной окраине села в урочище Прогон было найдено несколько поселений черняховской культуры; наиболее интересный комплекс находок происходит из поселения 2 и представлен в данной публикации. During the last years the archaeological club «Nevrida» of Tarashcha which is in the local department of the Children and Youth Central Association conducts archaeological reconnaissance near the Lukyanovka village of Tarashcha region. It was found the number of Chernichov culture settlements on the western outlying districts in the Prugon natural boundary; the most interesting complex of finds relates to the settlement 2 and represents in this publication.